A Structural Approach for Measuring Fiscal Disparities - Audun Langørgen; Rolf Aaberge (Statistics Norway, Research Department, 1999)
Fiscal disparities arise from differences in costs and capacity to produce a standard package of public services. This paper proposes to use a structural modelling approach as basis for measuring fiscal disparities across municipalities. This approach differs from the widely used reduced-form approach, in the sense that identification of minimum required costs or expenditure need is made by reference to a structural model of the fiscal and spending behavior of local governments. The empirical analysis, which is based on data for Norwegian municipalities, relies on various alternative measures of fiscal capacity. One of these measures is defined by the local tax-bases, whilst another also includes grants-in-aid from the central government. This facilitates identification of the equalizing effect from grants. By comparing the effects of the current grant system with the effects of a policy designed to reduce fiscal disparities it is demonstrated that the goal of locational neutrality is far from being fulfilled. Moreover, it is shown that differences in local priorities only give a minor contribution to the observed differences in service levels.
Keywords: H71; H72; 330; Local public finance; expenditure need; fiscal disparities; fiscal equalization